Russian culture through the prism of English, Finnish and Japanese languages: Reflections or refractions? - Elena V. Beloglazovaa; Natalia A. Osmak; Ekaterina K. Shuvalova (Peoples' Friendship University of Russia (RUDN University), 2024)
Thinning borders in the modern world result in intense translingual/transcultural communication. Yet, a language is originally fit to describe its own culture, while cultural reorientation requires considerable adaptation. The paper aims at researching the mechanisms of languages' cultural reorientation as exemplified by the Japanese-, English- and Finnish-language Russia-centred discourse. The cultural reorientation of a language is seen as a mode of translation - translation of culture. Research questions are: What linguistic techniques to introduce exocultural context are preferred by the focus languages? What elements of the source culture are selected for constructing the Russia-centred discourse in the focus languages? The research is based on data in three unrelated languages. The data is organised in manually annotated corpora of culturally loaded texts of book titles. The analysis of translation techniques employed by different languages in the process of cultural reorientation revealed (a) the specificity of the strategy of translating culture as contrasted to that of traditional translation; (b) the features of the exoculture-centred discourse as affected by language-specific linguistic factors. The study of xenonyms, selected to represent the source culture, shows a considerable variation in the choice of representatives, while the types of xenonyms are largely comparable. The cross-linguistic research of Russia-centred discourse is crucial for understanding established discursive canon, which must serve as guidance for presenting and promoting Russian culture in intercultural dialogue.